(untitled) (Filološke pripombe, 2019)
The article deals with some of the newer concepts in the theory of literary historiography with special emphasis on the interpretation of recent history of Slovenian literature, Slovenska književnost III. Interpretation examines how it relates to the traditional terms of literary historiography (teleology, linearity,chronology, the grand narrative etc.) and how is it cope with the latest concepts in the writing of literary history, does it take them into account or is it continues the traditional methods and concepts of literary history.